Barriers and Facilitators to Implement Preventive Practices to Drug Abuse - Monteiro, Erika Pizziolo; Gomide, Henrique Pinto; Costa, Pedro Henrique Antunes da; Silveira, Pollyanna Santos da; Ronzani, Telmo Mota (Paidéia (Ribeirão Preto), 2018)
In the Brazilian context, the Prevention Course to Drug Use for Public School Educators is developed. This study seeks to identify factors cited by the educators as favorable or unfavorable to the implementation of prevention projects. Data collection was carried out in three stages: in the first stage (T0), a sample consisted of 1494 course participants, in the second stage (T1), 2153 teachers participated and in the third stage (T2), 1017 educators answered the questions. Text mining techniques and content analyses were used. The results were categories proposed for the axes barriers and favorable aspects: training of school team, students and school community relationship and participation of the community and perceived dysfunctional family aspects, violence and drug trafficking, personal characteristics of adolescents and the school environment, respectively. The identification of these aspects is relevant to the development of prevention programs, allowing barriers to be anticipated and solutions to be proposed.